The Behavior of Government Vendor Project in Using E-Procurement System A Case Study of Construction Project Vendors in West Nusa Tenggara - PRAMDANA, HENDRA SATRIA; NURMANDI, ACHMAD (Jurnal Studi Pemerintahan, 2019)
E-procurement system is a procurement of goods/services implemented by using information systems and electronic transactions conducted by LPSE as an organizer and vendor as provider of goods /services. This study aims to predict and explain the determinants of interest in the behavior and behavior of users in using e-procurement by employees at construction companies that are suppliers for West Nusa Tenggara Provincial Government in the procurement system of goods/services. The research method used is quantitative method by distributing questionnaires to 114 respondents who work and have position as manager, assistant manager, supervisior and staff. This research develops Unified Theory of Acceptance and Use of Techonology (UTAUT) and Information System Success Model, then data is processed using Partial Least Square (PLS). The result of this research shows that performance expectancy, Effort expectation, system quality act as determinat interest behavior with value of RÂ² 0.441 while conditions that facilitate and interest behavior as determinant of behavior of usage with value RÂ² 0,277. Meanwhile, the results of the UTAUT model development and information success model in this study can explain and predict the uncertainty that often arises when individuals transact electronically through the E-procurement system.